1 g Shaking table test of segmental tunnel in sand under near-fault motions. (September 2021) - Yang, Yusheng; Yu, Haitao; Yuan, Yong; Sun, Jun
Highlights: 1 g shaking table test is conducted on a designed segmental tunnel in sand. The ground fundamental frequencies under different motions is observed. Comprehensive experimental results are recorded and analyzed in detail. Near-fault ground motions could remarkably amplify the ground and tunnel responses. The physical mechanisms behind the test data are further discussed. Abstract: A 1 g shaking table test is conducted to investigate seismic responses of a segmental tunnel in sand under near-fault motions. The tunnel model is assembled with segments, bolts and rubber strips and embedded in a shallow sand ground. The test facility, design and preparation of the tunnel model and the sand ground, as well as selected earthquake motions, are presented in detail. Dynamic responses obtained from the experiment include accelerations of the sand ground and the tunnel model, strains of segments, diametric deformations of the tunnel section, as well as bolt tensions and rotation of radial joints. Results show that the ground fundamental frequency changes with different input motions due to sand nonlinearities, and the deformation of the segmental tunnel is concentrated on radial joints. Moreover, near-fault motions would significantly aggravate the seismic response of both the sand ground and the segmental tunnel compared to far-field motions. Physical mechanisms contributed to the observation that near-fault motions would lead to larger shear strains of ground, especially when the ground fundamental frequency decreases, are also discussed.